The Effect of Liquidity and Profitability on Stock Returns: Evidence from IDX-Listed Automotive and Component Firms - Zulfitra; Jonnardi; Dessy Adelin (Jurnal Ilmiah Manajemen Kesatuan, 2026)
The development of the capital market encourages investors to evaluate corporate financial performance as a basis for investment decisions, particularly in the automotive and component sectors listed on the Indonesia Stock Exchange. This study aims to examine the effect of liquidity and profitability on stock returns of automotive and component companies during the 2018–2023 period. A quantitative approach was employed by applying panel data analysis using EViews 12 software. Liquidity was measured using the current ratio, while profitability was assessed through return on assets. The research data were obtained from the companies’ annual financial statements selected through purposive sampling. The findings indicate that liquidity has a positive influence on stock returns, suggesting that a firm’s ability to meet short-term obligations can enhance investor confidence. Furthermore, profitability shows a positive and significant effect on stock returns, implying that higher profit levels provide favorable signals to the market. Simultaneously, liquidity and profitability contribute significantly to the improvement of stock returns. These results strengthen fundamental financial theories and offer practical implications for investors in making informed investment decisions.